2022
DOI: 10.1186/s12939-021-01587-z
|View full text |Cite
|
Sign up to set email alerts
|

Intersectional inequalities in younger women’s experiences of physical intimate partner violence across communities in Bangladesh

Abstract: Background Physical intimate partner violence (IPV) risk looms large for younger women in Bangladesh. We are, however, yet to know the association between their intersectional social locations and IPV across communities. Drawing on intersectionality theory’s tenet that interacting systems of power, oppressions, and privileges work together, we hypothesized that (1) younger, lower educated or poor women’s physical IPV experiences will be exacerbated in disadvantaged communities; and conversely, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 85 publications
(109 reference statements)
0
4
0
Order By: Relevance
“…Research highlights that violence against women does not arise from individual deviancy; it is politically and structurally organized and a result of domination across various inequalities, including race or ethnicity, nationality, class, and gender (Valdovinos et al, 2021). Using intersectionality theory makes it possible to identify the structures and processes that place the victims of domestic violence in vulnerable situations and, at the same time, help policy-makers develop policies that address the socioeconomic and educational inequalities that help produce violence (Rahman et al, 2022). In exploring domestic violence among Latino immigrants, Valdovinos et al (2021) assert that, although their immigration status plays a substantial role in their lives, factors such as class, country of origin, and social location all shape their experience in the new country.…”
Section: Theory: Intersectional Feminism and Social Equitymentioning
confidence: 99%
See 2 more Smart Citations
“…Research highlights that violence against women does not arise from individual deviancy; it is politically and structurally organized and a result of domination across various inequalities, including race or ethnicity, nationality, class, and gender (Valdovinos et al, 2021). Using intersectionality theory makes it possible to identify the structures and processes that place the victims of domestic violence in vulnerable situations and, at the same time, help policy-makers develop policies that address the socioeconomic and educational inequalities that help produce violence (Rahman et al, 2022). In exploring domestic violence among Latino immigrants, Valdovinos et al (2021) assert that, although their immigration status plays a substantial role in their lives, factors such as class, country of origin, and social location all shape their experience in the new country.…”
Section: Theory: Intersectional Feminism and Social Equitymentioning
confidence: 99%
“…It was later expanded by McCall (2005), who developed an inter‐categorical approach that quantified the influence of different contexts. Intersectional feminism argues that human behaviour and experiences are a result of the interactive force of contexts or social structures and inequalities such as ageism, racism, sexism, and classism (Collins, 2017; Crenshaw, 2015; DeFelice & Diller, 2019; McCall, 2005; Rahman et al., 2022). Intersectional feminists treat power structures as being interconnected with various social identities, including race (or ethnicity), class, and gender, which also create the foundation for multi‐layered domination that determines access to power, privilege, influence, and social relationships (Valdovinos et al., 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, social norms and poverty were shown as core drivers that underlie lack of agency, lack of opportunity, and pregnancy/fear of pregnancy. The idea of interacting factors can be explained through ‘intersectionality’; it has been highlighted as one of the explanatory tools for child marriages (see e.g, Rahman et al., 2022). These drivers reflected community, household, and individual‐level factors (Psaki et al., 2021).…”
Section: Introductionmentioning
confidence: 99%